Analisis Penerapan Akuntansi Persediaan Berdasarkan SAK EMKM dan Pengendalian Persediaan yang Ekonomis pada Toko Benih Tamban Tani di Desa Kedawung, Kecamatan Mojo - Resa Putri Ningtias; Erna Puspita; Sigit Puji Winarko (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study discusses the application of inventory accounting in micro-enterprises, particularly at Toko Benih Tamban Tani, located in Kedawung Village, Mojo District. The main issue addressed is the suboptimal recording and calculation of inventory costs in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). As a vital component of business operations, inventory should be managed systematically to accurately reflect the financial position and support operational efficiency. This research employs a descriptive qualitative approach. Data were collected through interviews, observations, and the collection and analysis of relevant documents, complemented by quantitative calculations using the Economic Order Quantity (EOQ) method to assess purchasing efficiency. The analysis aimed to describe current practices and compare them to the standards set forth in SAK EMKM. The findings indicate that inventory recording is still performed manually without a formal accounting format, and several operational costs such as shipping fees, electricity, and other supporting expenses have not been included in the calculation of the cost of goods sold. Additionally, based on EOQ analysis, the actual purchasing frequency is higher than the optimal amount, indicating inefficiencies in inventory procurement.